2021
DOI: 10.18632/aging.203699
|View full text |Cite
|
Sign up to set email alerts
|

PPARα agonist relieves spinal cord injury in rats by activating Nrf2/HO-1 via the Raf-1/MEK/ERK pathway

Abstract: Objective: To observe the inhibitory effects of the peroxisome proliferator-activated receptor alpha (PPARα) agonist palmitoylethanolamide (PEA) on inflammatory responses and oxidative stress injury in rats with spinal cord injury (SCI). Methods: The SCI rat model was established using modified Allen's method and the changes in rats’ joint motion were observed by Basso, Beattie and Bresnahan locomotor rating scale (BBB scale) at 1, 3 and 7 days after modeling, HE Staining and Nissl Staining has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…Consistent with our study, a prior study revealed that activation of the Nrf2/HO‐1 pathway suppresses neuronal apoptosis and alleviates oxidative stress in SCI rats, 42 facilitating functional recovery in mice with SCI 43 . Importantly, prior research highlights the synergistic effects of the HO‐1 pathway and PPARα agonists in enhancing motor function and mitigating SCI in SCI rats 44 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with our study, a prior study revealed that activation of the Nrf2/HO‐1 pathway suppresses neuronal apoptosis and alleviates oxidative stress in SCI rats, 42 facilitating functional recovery in mice with SCI 43 . Importantly, prior research highlights the synergistic effects of the HO‐1 pathway and PPARα agonists in enhancing motor function and mitigating SCI in SCI rats 44 …”
Section: Discussionsupporting
confidence: 90%
“…43 Importantly, prior research highlights the synergistic effects of the HO-1 pathway and PPARα agonists in enhancing motor function and mitigating SCI in SCI rats. 44 Limitations and Strengths However, a notable limitation is the minimal exploration of FTO's downstream targets and specific pathways of action, a focus for future research. Due to constraints in laboratory conditions and funding, electromyography data is currently unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…During oxidative stress, the interaction between NRF2 and Keap1 in the cytoplasm is disrupted [ 48 ]. NRF2 translocates to the nucleus and interacts with ARE, leading to the transcriptional induction of some cell defense genes, such as phase II detoxification enzymes HO-1, NQO1, and direct ROS scavenging proteins (GPx, SOD, CAT) [ 49 , 50 ]. Many studies have confirmed that activation of NRF2 can prevent damage caused by ferroptosis [ 14 , 24 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glycogen synthase kinase‐3β (GSK3β), a serine/threonine protein kinase, is a multifunctional regulator of mitochondrial function (Wang et al, 2021). Inhibition of GSK3β activity attenuates oxidative stress‐induced mitochondrial dysfunction and apoptosis (Gao et al, 2017; He et al, 2019; Huang et al, 2017; Mao et al, 2019; Potz et al, 2018; Wang et al, 2015; Zhang et al, 2021). When the intracellular oxidative system exceeds antioxidant capacity, reactive oxygen species accumulate (ROS) and oxidative stress increases (Hardy et al, 2021).…”
Section: Introductionmentioning
confidence: 99%